Gastric lipomatosis treated by total gastrectomy: a case report - Shota Aoyama; Katsunori Ami; Akira Fukuda; Kenichiro Imai; Ja-Mun Chong; Masayuki Ando (Surgical Case Reports, 2017)
Abstract Background Gastric lipomatosis is characterized by multiple gastric lipomas or a diffuse gastric infiltration of the submucosal or subserosal layer by the adipose tissue; diffuse-type gastric lipomatosis is an extremely rare condition. Here, we present the case of a patient with gastric lipomatosis treated by total gastrectomy. Case presentation A 54-year-old man diagnosed with gastric submucosal tumor in 2008 was referred to our hospital for further examination and treatment in September 2016. Upper gastrointestinal endoscopy revealed a submucosal tumor with an associated ulcer on the anterior wall of the lower body of the stomach. A compressing mass was observed on the anterior wall of the greater curvature and the posterior wall of the stomach. Following a biopsy of the submucosal tumor and ulcer, lipoma without malignancy was diagnosed by microscopy. A giant gastric lipoma was suspected because endoscopic ultrasound revealed a high-echoic lesion on the antral wall that extended to the stomach. Therefore, total gastrectomy was performed, and gastric lipomatosis was confirmed by a histological examination of the resected specimen. Conclusions Surgical treatment is a highly effective treatment for symptomatic gastric lipomatosis with extensive involvement or multiple lipomas and can be used for patient diagnosis.